Chronic Life Stress, Cardiovascular Reactivity, and Subclinical Cardiovascular Disease in Adolescents - Low, Carissa A. (2009)
OBJECTIVE: To examine cross-sectional and longitudinal relationships between chronic life stress, cardiovascular reactivity, and a marker of subclinical cardiovascular disease in a multiethnic sample of adolescents. METHODS: Participants were 158 healthy adolescents who completed self-report measures of chronic negative life stress as well as assessments of heart rate and blood pressure reactivity to acute laboratory stressors at two timepoints, approximately 3.3 years apart. At Time 2, intima-media thickness (IMT), a measure of subclinical atherosclerosis, was also measured. RESULTS: In hierarchical regression models adjusting for demographic variables and body mass index, chronic negative life stress at Time 2 was concurrently associated with greater diastolic blood pressure (DBP) reactivity to stress (β = 0.18, p = .016), but neither chronic stress nor cardiovascular reactivity was concurrently associated with IMT. Increasing life stress from Time 1 to Time 2 was accompanied by increasing cardiovascular reactivity (β’s = 0.14 to 0.20, p < .05), and increasing DBP reactivity over time was also associated with IMT (β = 0.24, p = .03), though increasing chronic life stress was not directly related to IMT. CONCLUSIONS: Adolescents exposed to chronic, negative stressors that worsen over time may show heightened cardiovascular reactivity that puts them at risk for subclinical atherosclerosis.